Penerapan Metode Penemuan Terbimbing untuk Memahami Konsep Aturan Sinus, Kosinus, dan Luas Segitiga di Kelas X MIA 3 SMAN 10 Padang - Rosalina Rosalina (Journal on Education, 2023)
This Classroom Action Research aims to improve students' understanding of the concepts of the Rules of Sine, Cosine, and Area of Triangles by applying the Guided Discovery method to mathematics learning. The research procedure uses Classroom Action Research (CAR) with several cycles. Each cycle includes four stages, namely planning, implementation, observation, and reflection. The research subjects were 32 students of class X MIA 3 SMAN 10 Padang in the 2018/2019 academic year even semester as many as 32 people. Data from research results: completeness in the first cycle is 62.5%, increasing in the second cycle is 84.4% complete. Overall there was an increase from cycle I to cycle II. Thus, it can be concluded that: The Guided Method of Mathematics Learning can Improve Concept Understanding of Class X MIA 3 SMAN 10 Padang Students